Micropolitics of middle managers in influencing centre-led change initiative: case study of a Malaysian based MNC - Nizam Abdullah,; Mohd Nazari Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The purpose of this article is to explore the micropolitics of middle managers in influencing the development and outcome of a centre-led change initiative. This study was empirically based on a novel context in a Malaysia based multinational company (MNC) and four of its Asian subsidiaries. This qualitative study was conducted through a multiple embedded case study approach. The findings demonstrate that middle managers have within their powers to influence the development and eventually the outcome of change. This was achieved through control of middle managers on resources such as business knowledge and networking in influencing the meaning of change itself. This article allows the authors to investigate an in-depth exploration of how subsidiary managers operate. It contributes to the change literature by expanding the knowledge about the tight coupling between power and politics of organizational sensemaking.